A Quick Look at Mobile Game Development - Suhendra Suhendra (IC-ITECHS, 2020)
Every person these days has a mobile phone, so it is no surprise the mobile game market has skyrocketed. Additionally, the rising number of mobile devices worldwide will result in an estimated 4.78 billion mobile users worldwide by 2020. Gaming industry worldwide is expanding, and smartphone is playing a significant role in this expansion. The development of mobile games has resulted in scalability for the gaming industry. The growing smartphone penetration and technology advancement with the increasing adoption of trending technologies for developing games are some major factors developing the market for the mobile gaming industry. With the changing perception of phones as a technology for everyone, a new possibility for game development emerged. Game development is not seen as something only a few trained people or multi-million dollar company can do. With the help of technology and the internet, everyone has easy access to it. People can learn about game development from scratch even without having mentors or classes. Knowing all the possibilities and opportunities, as students majoring in the IT fields, there is a promising future career path. Along with learning the usual materials taught in college, mobile game development will definitely give a huge impact. Students can do it as an additional skill set for what they are studying and also as a step towards being a game developer. This webinar was held as an introduction of mobile game development to students to also encourage them to start developing one.